Pituitary adenylate cyclase-activating polypeptide 6-38 blocks cocaine- and amphetamine-regulated transcript Peptide-induced hypophagia in rats. - Jonathan R Burgos (Public Library of Science (PLoS), 2013)
Cocaine- and amphetamine-regulated transcript peptides (CARTp) suppress nutritional intake after administration into the fourth intracerebral ventricle. Recent in vitro studies have shown that PACAP 6-38, a pituitary adenylate cyclase-activating polypeptide (PACAP) fragment, could act as a competitive antagonist against CARTp 55-102 on a common CARTp-sensitive receptor structure. Here, we show for the first time in vivo that the reduction in solid food intake induced by exogenous CARTp 55-102 (0.3 nmol: 1.5 µg) administered fourth i.c.v. is blocked by pretreatment with PACAP 6-38 (3 nmol). The PACAP 6-38 fragment had no effect by itself either when given into the fourth ventricle or subcutaneously. Although effective to block the CARTp-effect on feeding and short-term body weight, PACAP 6-38 failed to attenuate CARTp-associated gross motor behavioral changes suggesting at least two CARTp-sensitive receptor subtypes. In conclusion, PACAP 6-38 acts as a functional CARTp antagonist in vivo and blocks its effects on feeding and short term weight gain.